The Impact of the Institutional Factors in the Public Sphere on Export in OECD Countries - Ozmen, Alper; Saritas, Tufan (Public Finance Quarterly, 2021)
As it is known, export is a positive economic phenomenon that is desired to be realized for all countries. From this point of view the effect of institutional factors in the public sphere on export was investigated in 36 OECD countries for the period between 2002-2018. Four different models were established in the study and export was defined as the dependent variable in all models. In the first model it is determined that there is a negative relationship between the control of corruption and export. In the second model it was determined that there is an inverse relationship between regulatory quality and export. In the third model it is observed that there is a similar relationship between political stability and exports. In the fourth model that investigates the possible effect of the rule of law on exports there was no statistically significant relationship between the relevant variables.